The Significant Terminology of Waswas on Obsessive-Compulsive Disorder - Mohd Zahir Abdul Rahman; Zul Azlin Razali; Robiatul Adawiyah Mohd@Amat; Shah Rizul Izyan Bt Zulkiply; Mohd Zohdi Mohd Amin (Universiti Putra Malaysia, 2024)
The term waswas was used five times in the Quran and seven times in 7 Kutub Hadith. Its interpretations given by exegetes and scholars in Islamic studies are various and one of them is related to obsessive-compulsive disorder (OCD). This is a study of the term waswas with the specific goal to identify its elements that are in parallel with a modern understanding of OCD. This is a qualitative study which employs content and document analysis of selected Islamic exegesis of the al-Quran, Hadith and traditional scholar opinions focusing on three aspects of OCD; obsession, compulsive behavior and causes. Al-Quran and Hadith is the final miracle that encompasses geographical and generational limits. Even though OCD seems to be a diagnosis of modern days, its essences were mentioned in the great Al-Quran.